Hyperhomocysteinemia due to Vitamin B12 Deficiency with MTHFR Gene Mutation, an Atypical Metabolic Cause of Young Ischemic Stroke: A Case Report - Qayyum, Junayed Abdul; Sayeed, S K Jakaria Been; Ahmed, Fatema; Sarker, Poritash Kumar; Mahmud, Reaz (Journal of Medicine, 2023)
Background: Vitamin B12 deficiency can impair the metabolism of homocysteine, leading to hyperhomocysteinemia that can cause thrombosis in the intracranial blood vessels resulting in a stroke. Case Presentation: A 15-year-old Muslim young boy initially presented with pallor, slurred speech, right facial weakness, and right-sided hemiplegia. On examination, he was found moderately anemic, nonicteric, and with right-sided stroke evidenced by hypertonia, reduced muscle power jerk exaggerated with extensor plantar response. There was no lymphadenopathy, bony tenderness, intellectual impairment, or organomegaly, and normal vital parameters with the unremarkable cardiovascular examination. Laboratory investigations revealed pancytopenia, with reduced Vit B12, folic acid, and moderately increased homocysteine level. Bone marrow study suggestive of megaloblastic anemia. Immunological, infectious screens; and prothrombotic markers were found negative. CT scan of the head revealed a hypodense lesion in the left parieto-occipital region, DWI sequence on MRI Brain revealed diffusion restriction in the same area while an MR angiogram of the Brain revealed occlusion of the left middle cerebral artery due to thrombus sparing a small segment after its origin. In addition, he had MTHFR c677 C>T (Methyl tetrahydrofolate reductase) gene mutation and responded both clinically and biochemically after vitamin B12, folic supplementation along with aspirin in 5 months. Conclusion: Vitamin B12 deficiency along with MTHFR c677 C>T gene mutation has increased the chance of thrombotic stroke. Vitamin B12 supplementation might be beneficial for patients with an MTHFR gene mutation positive. J MEDICINE 2023; 24: 51-55